Analysis of Factors Affecting the Green Purchase Intention of Electric Motorcycle: Case Study of Selis - Devin Pathavi; Mochammad Riyadh Rizky Adam; Yosman Bustaman (ADI Publisher, 2020)
Although Selis brand under PT.JUARA BIKE has been the pioneer of electric bicycle in Indonesia since 2011, the brand still has lack of demand on the electric motorcycle. The objective of this research is to analyze the factors affecting the green purchase intention of electric motorcycle. Some logical frameworks of this research are Subjective Norms, Aesthetic Value, Green Value, Perceived Price, and Perceived Quality. By using an online survey, a total of 300 respondents from people live in Jabodetabek region were collected. The findings showed that subjective norms, aesthetic value, green value, Perceived Price, and perceived quality influenced green purchase intention positively. The findings also revealed that green value, perceived quality and aesthetic value made the largest contribution in influencing green purchase intention among consumers. On the other hand, Perceived Price and subjective norms had a lesser significant impact on consumer intention to purchase green products.